(untitled) (American Journal of Arts and Human Science, 2023)
The purpose of this study is to discover how spiritual formation in Bocaue transforms the lives of the youth and how it strengthens their faith in God. Anchored in this study are John Fisher’s Four Domains of Spirituality, Health, and Well-Being and Soren Kierkegaard’s Three Stages of Life. The study was qualitative-phenomenological research with semi-structured interviews and purposive sampling. The interviews were transcribed verbatim and significant statements were chosen. These were categorized into theme clusters in order to get the emergent themes. The emergent themes reflected in the interviews were: Assimilation of Spiritual Formation, Justification of Spiritual Engagement, Before-and-After of Spiritual Engagement, and the Experiences in the Youth Ministry. The significant statements were carefully analyzed and categorized into themes. The following conclusions were drawn: (1) The youth sees the youth ministry and the spiritual formation as a platform for them to change for the better; (2) There are different reasons why the youth are joining the youth ministry by the influence of others, trained by the school, overcoming problems and personal growth; (3) The lives of the youth became better when they started their service in the church and; (4) The youth ministry truly transforms the lives of the young people in many aspects.